العوامل المؤثرة في جودة العملية التعليمية في قسم المحاسبة من وجهة نظر أعضاء هيئة التدريس: دراسة تطبيقية على قسم المحاسبة/ كلية الاقتصاد والمحاسبة/ جامعة سبها/ ليبيا (Journal of Academic Research, 2019)
The aim of this study is to identify factors that may affect the quality of the educational process in the Accounting Department, Faculty of Economics and Accounting / University of Sabha, from the point of  view of the members of the teaching staff.To achieve the objectives of the study, a questionnaire form was prepared and distributed to a sample of Lecturers at the accounting department.The study showed several results, the most important of which is that the factors studed affected the quality of the educational process in the accounting department, according to the studied elements, the affect was  varied  between the high and intermediate and low degree from the point of view  the of lecturers'.The study has reached several recommendations, the most important one is that, the emphasize on adopting an integrated and clear strategy to raise the quality of the educational process, including all the policies set out, the objectives to be achieved and the binding procedures.